Towards experimental investigation of hosing instability mitigation at the PITZ facility. (July 2020) - Loisch, G; Gross, M; Koschitzki, C; Lishilin, O; Ossa, A Martinez de la; Osterhoff, J; Stephan, F
Abstract: Beam-driven plasma wakefield acceleration (PWFA) allows for high gradient acceleration of electron beams and hence is a promising candidate for compact and cost-efficient drivers of applications demanding high brightness beams. One of the main challenges in these accelerators is to control beam-plasma instabilities with rapid growth rates which are induced by the strong transverse components of the wakefields. The hosing instability, a growing transverse oscillation of the beam centroid caused by coherent coupling between bunch slice centroids and transverse wakefields, was predicted to set severe limits on the possible acceleration distance in PWFAs. Several methods have been proposed to damp or even suppress the hosing of the beam, prevent beam-breakup and thus allow stable operation. Here, we present preparations and simulation studies aiming at the experimental investigation of hosing suppression mechanisms at the PITZ facility.